A single amino acid at position 158 in haemagglutinin affects the antigenic property of Eurasian avian‐like H1N1 swine influenza viruses. Issue 4 (24th August 2021) - Wang, Zeng; Chen, Yan; Chen, Huayuan; Meng, Fei; Tao, Shiyu; Ma, Shujie; Qiao, Chuanling; Chen, Hualan; Yang, Huanliang
Abstract: Influenza viruses have been posing a great threat to public health and animal industry. The developed vaccines have been widely used to reduce the risk of potential pandemic; however, the ongoing antigenic drift makes influenza virus escape from host immune response and hampers vaccine efficacy. Until now, the genetic basis of antigenic variation remains largely unknown. In this study, we used A/swine/Guangxi/18/2011 (GX/18) and A/swine/Guangdong/104/2013 (GD/104) as models to explore the molecular determinant for antigenic variation of Eurasian avian‐like H1N1 (EA H1N1) swine influenza viruses (SIVs) and found that the GD/104 virus exhibited 32‐ to 64‐fold lower antigenic cross‐reactivity with antibodies against GX/18 virus. Therefore, we generated polyclonal antibodies against GX/18 or GD/104 virus and a monoclonal antibody (mAb), named mAb102‐95, targeted to the haemagglutinin (HA) protein of GX/18 virus and found that a single amino acid substitution at position 158 in HA protein substantially altered the antigenicity of the virus. The reactivity of GX/18 virus containing G158E mutation with the mAb102‐95 decreased eightfold than that of the parental strain. Contrarily, the reactivity of GD/104 virus bearing E158G mutation with the mAb102‐95 increased by 32 times as compared with that of the parental virus. Structural analysis showed that the amino acid mutation from G to E was accompanied with the R group changing from ‐H to ‐(CH2 )2 ‐COOH. The induced steric effect and increased hydrophilicity of HA protein surface probably jointly contributed to the antigenic drift of EA H1N1 SIVs. Our study provides experimental evidence that G158E mutation in HA protein affects the antigenic property of EA H1N1 SIVs and widens our horizon on the antigenic drift of influenza virus.